RELATIONSHIP BETWEEN BODY MASS INDEX AND ACTIVITIES OF DAILY LIVING ELDERLY IN RURAL COMMUNITIES - Susanto, Joko; Rukanah, Rukanah; Iswatun, Iswatun (Journal of Vocational Nursing, 2024)
Introduction: A high Body Mass Index (BMI) is known to be associated with mortality and morbidity in the elderly. However, other studies also show the opposite results regarding high BMI as a protector against Activity Daily Living (ADL). Accurate quantification of the role of BMI in the incidence of disability in ADL. Given the increasing prevalence of overweight and obese individuals and the long life spans in the population. This study aims to determine the relationship between Body Mass Index and Daily Life Activities in population-based elderly people. Methods: The method used in this research is a cross-sectional observational study conducted on 167 respondents from rural areas in the Lamongan Regency, using a consecutive sampling approach. BMI scores and the Barthel Index were recorded among respondents. Data were analyzed using the Spearman Test with a significance level of p<0.05. Results: A total of 167 respondents came from rural areas in Lamongan Regency, dominated by 96 (57.5%) women and 71 (42.5%) men. The Spearman Test results found a weak and significant positive correlation between body weight and daily activities (r= 0.167; p<0.05). Apart from that, a significant weak positive correlation was also found between BMI and ADL (r= 0.157; p<0.05). Conclusions: The results of the study show that increasing the BMI value has a protective effect on ADL, so it can be concluded that higher body weight and BMI are associated with increasing Barthel ADL scores.